Aktywność promocyjna gmin wiejskich województwa łódzkiego - Marks, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The article represents some of the results of research on the promotion activity of rural communities. The empirical background of my deliberations makes terrain investigations, conducted within the first half of the year 2002 among the local authorities of rural communities of Lodz province. The analyses results confirm that rural communities addresses promotion activities mainly to local communities promoting the local social-product. Generally, they use direct communication canals to peruse that. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 341-348